Biochemical composition and antioxidant capacity of two sea cucumbers (Cucumaria frondosa and Parastichopus tremulus) - Edvardsen, Celine (UiT The Arctic University of Norway, 2020)
Sea cucumber is one of the most expensive seafood products in the world and dried sea cucumbers can be valued at more than USD 300 per kilogram for Astichopus japonicus, which is one of the highest priced species. Both market and consumption are centred in East- Asia. Sea cucumbers are sold in various forms, but the majority are distributed to the ’beche-de-mer’ market (gutted, boiled and dried body wall of sea cucumber). Norway has a long history as a seafood nation and has set new export records every year since 2012, but has no commercial harvest of sea cucumbers. They mostly occur as by-catch during shrimp trawling and crayfish fishing in the fjords. The Norwegian Government has set a goal to increase economic growth for new marine species. Out of the 31 species of sea cucumber along the Norwegian coast, Norwegian red sea cucumber (Parastichopus tremulus) and Orange-footed sea cucumber (Cucumaria frondosa) are considered to be the species of interest for the Asian market. Especially P. tremulus, as it belongs to the same family as preferred species A. japonicus. Based on market feedback, the estimated price potential for dried Norwegian sea cucumber is NOK 1000-2000 per kilogram. The analyses in this study were conducted on freeze-dried material and were recalculated to wet weight. The amount of fat, protein, water and ash was analysed, including analyses of amino acid composition and fatty acid composition. Analyses were also made of antioxidant capacity in the sea cucumber species. Significant differences were found for the proximate composition between the sea cucumber species in this study, for example, the fat content was 0:4% for P. tremulus and 2:0% for C. frondosa. The composition of fatty acids were similar for both species, with the highest content of PUFA followed by MUFA and SFA respectively. Both species had a favourable ratio of n-6:n-3 fatty acids, but only C. frondosa complied with the daily recommendation of EPA and DPA by consuming 100 grams of sea cucumber. The protein content was higher ...